2009
DOI: 10.1007/s10389-009-0286-1
|View full text |Cite
|
Sign up to set email alerts
|

Mobile phone use while driving: a major public health problem in an Arabian society, State of Qatar—mobile phone use and the risk of motor vehicle crashes

Abstract: Aim The aim of the present study was to assess the rate of mobile phone use among drivers who were involved in road traffic crashes and to determine the factors associated with mobile phone use in Qatar. Methods Structured interviews were conducted and participants were asked to complete a questionnaire concerning socio-demographics, driving attitudes and behaviour, adherence to traffic laws and mobile phone use. The study was conducted from December 2004 to June 2005 during which 1,139 drivers were asked to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 33 publications
1
12
1
1
Order By: Relevance
“…This is consistent with the observational study conducted at two universities in Qatar where the prevalence of seat belt use among students driving SUVs was 34.1 %, compared to 53.4 % of students driving non-SUV vehicles [ 14 ]. Similar trends were also noted in another Qatari study using self-reports, where 67 % of small car drivers reported mobile phone use while driving, compared to 83 % of SUV drivers [ 24 ]. Similarly, SUV drivers in the United Arab Emirates (UAE) were found to be less likely to use the seat belt and more likely to commit traffic violations than non-SUV drivers [ 28 ], and similar trends were also observed in the United Kingdom [ 29 ].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…This is consistent with the observational study conducted at two universities in Qatar where the prevalence of seat belt use among students driving SUVs was 34.1 %, compared to 53.4 % of students driving non-SUV vehicles [ 14 ]. Similar trends were also noted in another Qatari study using self-reports, where 67 % of small car drivers reported mobile phone use while driving, compared to 83 % of SUV drivers [ 24 ]. Similarly, SUV drivers in the United Arab Emirates (UAE) were found to be less likely to use the seat belt and more likely to commit traffic violations than non-SUV drivers [ 28 ], and similar trends were also observed in the United Kingdom [ 29 ].…”
Section: Resultssupporting
confidence: 82%
“…In the current study, approximately 8 % of drivers were observed using handheld mobile phone devices while driving. This point prevalence is lower than self-reported prevalences of drivers in Qatar; in one study, 73 % of drivers involved in a MVC in Qatar reported that they sometimes use a mobile phone while driving [ 24 ], whereas in another, 42 % reported using a mobile phone for calls while driving and 20 % admitted to texting while driving [ 12 ]. Studies in other high-income locations, which applied a similar methodology to this study reported lower rates of mobile phone use while driving than in Doha.…”
Section: Resultsmentioning
confidence: 99%
“…There was a sudden growth in population in rich developing countries including many different nationalities and ethnic and/or immigrant groups which also leads to an increase in vehicle demand. Studies conducted in Qatar ( Bener, Crundall, Haigney, Bensiali, & Al-Falasi, 2007 ; Bener & Crundall, 2008 ; Bener, Ozkan, & Lajunen, 2008 ; Bener, Crundall, Özkan, & Lajunen, 2010 ) showed an increasing trend in road traffic accidents and different types of driver behaviour causing accidents among Qatari drivers. The findings of the previous studies ( Bener et al, 2007 ; Bener & Crundall, 2008 ) have also shown that self-reported driving behaviours are associated with both active and passive traffic accidents among other drivers in different countries.…”
Section: Introductionmentioning
confidence: 99%
“…Some drivers in affluent developing societies have dangerous behaviours and are not fully aware of the impact of these on safety [14,21,22]. For example, there is evidence that the national rate of seatbelt wearing is very low (only 22.0%) [9] and there is widespread use of mobile phones while driving [21,22]. Educational programmes to raise the young's awareness about the impact of RTA injuries and fatalities on their vulnerable age, and their consequences on themselves, their families and the country should be introduced.…”
Section: Discussionmentioning
confidence: 99%